2015
DOI: 10.1002/jat.3221
|View full text |Cite
|
Sign up to set email alerts
|

Human ketosteroid receptors interact with hazardous phthalate plasticizers and their metabolites: an in silico study

Abstract: Phthalic acid esters or phthalates are ubiquitous environmental pollutants known for their adverse health effects in test animals and, of late, in humans. Thus, in this molecular docking study - using Glide (Schrödinger) - the molecular interactions of 31 ligands, including 12 diphthalates, their monophthalates and phthalic acid with selected human ketosteroid receptors, i.e., androgen (hAR), progesterone (hPR) and glucocorticoid (hGR) receptors were explored and their binding affinities were compared with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…DEHP and MEHP were predicted to have high binding affinities for the RXRs, particularly the human RXRα (Sarath Josh et al ., ). Similar docking studies have also shown interactions between phthalates and the human androgen, progesterone, and glucocorticoid nuclear receptors (Sarath Josh et al ., ). Whether DEHP or its metabolites plays a significant role by directly or partially interacting with these nuclear receptors needs to be experimentally confirmed.…”
Section: Di(2‐ethylhexyl) Phthalatementioning
confidence: 97%
“…DEHP and MEHP were predicted to have high binding affinities for the RXRs, particularly the human RXRα (Sarath Josh et al ., ). Similar docking studies have also shown interactions between phthalates and the human androgen, progesterone, and glucocorticoid nuclear receptors (Sarath Josh et al ., ). Whether DEHP or its metabolites plays a significant role by directly or partially interacting with these nuclear receptors needs to be experimentally confirmed.…”
Section: Di(2‐ethylhexyl) Phthalatementioning
confidence: 97%
“…Phthalates act as agonists or antagonists on the NRs [ 52 ]. In silico studies observed a high affinity of some phthalates to NRs: DPhP, MBzP, MEHP, BBzP, mono-(2-propylheptyl) phthalate (MPhP) to hAR [ 225 ], DINP, DPhP, BBzP, MPhP, DnOP to hERα; MPhP, MEHP, MnHP to hERβ [ 226 ], DINP, DnDP, DEHP, DnOP, BBzP, DPhP, DDP to hPPARα; DiDP, DnDP, mono-iso-decyl phthalate (MIDP), DINP, MEHP to hPPARγ [ 227 ]. Moreover, the study by Kambia et al [ 228 ] showed that the metabolites of the phthalate substituent–terephthalate, MEHHT, also had a higher affinity to ER and AR.…”
Section: Intracellular Signaling Mechanisms Of Phthalates’ Action mentioning
confidence: 99%
“…Final optimization and minimization were performed as described in the Schrödinger Protein Preparation Wizard (PrepWizard). The preparation protocol added hydrogen, built side chains and loops with missing atoms, optimized the H‐bonding network and performed a restrained minimization to obtain the final structure of proteins for docking studies (Sarath Josh et al ., , , ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, screening of phthalates as a potential ligand of hPXR would provide valuable information for pharmaceutical, as well as toxicological research. Molecular docking as an efficient tool in predicting the possible interactions between target receptors and phthalates for assessing the molecular cross‐talks within human systems has been reported previously (Sarath Josh et al ., , , ); such insights would enable us to assess the receptor activating or non‐activating capacity of the ligands under study. A literature survey showed the lack of in silico studies on the hazardous phthalates and their primary metabolites by depicting the interactions with the hPXR, thereby examining the ligand interactions of hazardous phthalates would be beneficial.…”
Section: Introductionmentioning
confidence: 99%